The relationship between workplace environments and the level of employees productivity at Pejabat Setiausaha Kerajaan Pahang / Faizatul Akma Hamzah - Hamzah, Faizatul Akma (Faculty of Business & Management, 2017)
This study is to recognize the relationship between workplace environmental features toward employee's productivity among employees Pejabat Setiausaha Kerajaan Pahang (SUK). The research question has becn studied, I.The significant relationship between space planning, work environment and colors with employee's productivity, 2. The most of the workplace environmental features being provided by the company. 3. The least of the workplace environmental features being provided by the company. Lastly, 4. The level of employee's productivity. This study used descriptive correlative method. The sample sizes are taken 123 respondents and number of population 180 as stating from the sample size for a given population by Krejcie and Morgan (2006). The sampling technique used are simple random sampling, whereas, the researcher choose this technique due to its least bias and its offer the most generalizability on the selection of the respondents. The research findings can be concluded that there is positive relationship between workplace environmental features and employee's productivity.